Impact of mobile broadband on non-life insurance industry in Thailand and Singapore - Seksiri,N. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. This study investigates whether the non-life insurance industries in Thailand and Singapore are growing by the usage of mobile broadband technology. It examines the impact of the third generation (3G) mobile phone in Thailand and compares the same to the impact in Singapore as a benchmark. It also figures out the impact of the fourth generation (4G) mobile phone in Singapore to learn the impact that may occur in Thailand after the country begins to offer the service later. It uses the piecewise regression to analyze the trend before and after those countries adopted the mobile technologies. The results show that the mobile broadband both in terms of 3G and 4G technologies does not significantly affect the growth of the non-life insurance industry in both countries. They reveal that the insurance companies are incapable of catching up with the “mobile integration” to such a degree that they can use the mobile broadband to create opportunity, boost sales, and make profit for their businesses. Insurance companies should emphasize their priorities in order to encourage their customers to access information regarding their products, purchase their products, and notify any accidents or incidents on a real-time basis viamobile broadband. These strategies will enhance the impact of mobile broadband technology on the non-life insurance industry and empower the industry to grow in the era of the mobile broadband.